THE CONCEPT OF PHRASEOLOGICAL ETYMOLOGY AND ITS RESEARCH CRITERIA (Web of Teachers: Inderscience Research, 2026)
In this scientific article, we will first examine the essence of the concept of phraseological etymology and the origin, historical roots, and sources of formation of phraseological units of the language, i.e. idioms, phrases, and stable word combinations, from a linguistic perspective.